On Szász-Mirakyan type operators preserving polynomials - Gurel Yilmaz, Ovgu; Aral, Ali; Taşdelen Yeşildal, Fatma (J. Numer. Anal. Approx. Theory, 2017)
In this paper, a modification of Szász-Mirakyan operators is studied [1] which generalizes the Szász-Mirakyan operators with the property that the linear combination \(e_2 + α e_1\) of the Korovkin’s test functions \(e_1\) and \(e_2\) are reproduced for \(α≥ 0\). After providing some computational results, shape preserving properties of mentioned operators are obtained. Moreover, some estimations for the rate of convergence of these operators by using different type modulus of continuity are shown. Furthermore, a Voronovskaya-type formula and an approximation result for derivative of operators are calculated. Finally, some graphics which are based on our main results are shown.